A STUDY ON THE ALLOCATION OF FOREIGN AID AND THE EFFECT ON AFRICAN ECONOMIES AND REASONS FOR UNDERDEVELOPMENT DESPITE THIS AID - Monte Edwin Bota (2021)
The issue of Foreign Aid and lack of proper development of African and most of the developing word bothers many. A lot of papers have been written to try and figure this out for many specific economies in various countries. Millions of dollars are disbursed every year from the donors and development banks to the recipient countries for the purpose of development, but the situation is never changing which leads us to the question of what really happens to these funds. This paper seeks to review literature on the allocation of foreign aid and the mystery that surround the execution of development plans that the funds are meant for. The main set back is corruption and bad leadership, and this could solve all development problems for these African economies if they were worked upon and rectified. From this analysis it seems the gap in leadership and leadership could be filled with good transparent systems and knowledge about foreign aid made available for individuals and instructions and this is the answer to development and aid for the continent. The literature review acknowledges the disconnect between allocation of funds and lack of results to show for this in African Economies and the issues happening around Foreign Aid, and of course recommendations for possible solutions.